Pembentukan Karakter Wirausaha pada Gen Z menghadapi Society 5.0 - Ceria Febiana; Lydia Goenadhi; Imam Suharto; Anita Putri Wijayanti (Universitas Batanghari Jambi, 2023)
This study aims to determine the understanding of gene z on entrepreneurial character. This understanding of entrepreneurial character makes the foundation for Gen Z to face society 5.0. This character formation aims to prepare Gen Z to become better entrepreneurs in the future. This study uses a quantitative descriptive method, providing an overview of understanding the character of entrepreneurship. Respondents were students and college students aged 17 -20 years who came from Bandung. There are 12 characters are used as indicators of entrepreneurial character. 141 respondents were given a questionnaire using google forms, using a Likert scale to calculate the understanding score. The results of the total scores were searched for the average seen that gene z's understanding of an entrepreneurial character. The characters that are best understood by genes select goals/goals and initiatives. While the characteristic that is poorly understood by gen z is the desire to take risks and the willingness to learn. The strengthening of the entrepreneurial character in gene z is overall quite well understood and the gene can understand the overall character well.